Luteolysis, progesterone, and pregnancy per insemination after modifying the standard 7-day Ovsynch program in Holstein-Friesian and Holstein cows - Atanasov, B; Dovenski, T; Celeska, I; Stevenson, J S (American Dairy Science Association, 2021)
Two experiments were conducted with Holstein-Friesian cows in the Republic of North Macedonia and with Holstein cows in Kansas. We hypothesized that 1 dose of PGF2α administered on d 8 (Ov-8×1) instead of d 7 (Ov-7×1) in an Ovsynch program [GnRH-1 (d 0)-7 d-PGF2α-56 h-GnRH-2-16 h-timed artificial insemination (AI)] would increase the proportion of cows with complete luteolysis compared with controls receiving a single dose on d 7. Cows were treated with Ov-7×1 or with Ov-8×1 in experiment 1 (n = 347), using only a single dose of PGF2α. In experiment 2 (n = 452), a third treatment was added (Ov-7×2), in which a second dose of PGF2α was administered on d 8. Progesterone was measured in blood samples collected before the first or only PGF2α administration and 72 h later before insemination. Complete luteolysis was defined as having occurred when progesterone was ≥1 ng/mL before PGF2α and ≤0.3 ng/mL 72 h later (time of AI). Follicles and luteal structures were mapped before GnRH-1 and PGF2α administrations. The results of experiment 1 demonstrated a greater percentage of multiparous cows in OV-8×1 having complete luteal regression compared with multiparous Ov-7×1 cows, whereas treatments were equally effective in primiparous cows, as reflected in the concentrations of progesterone before AI. Furthermore, pregnancy per AI did not differ between treatments. Results in experiment 2 revealed that 99.3% of cows in the Ov-7×2 treatment receiving the second dose of PGF2α had complete luteolysis, regardless of parity, compared with significantly fewer cows in the Ov-7×1 and Ov-8×1 treatments (91.2 and 90.6%, respectively). Neither concentrations of progesterone, which averaged <0.4 ng/mL at AI, nor pregnancy per AI differed among the 3 treatments. In both experiments, when status of luteal function before PGF2α treatment was examined [cows with no corpus luteum (CL) before GnRH-1 but which had formed a new CL in response to ovulation after GnRH-1; cows with an older CL (the same CL that was detected before GnRH-1); or cows with both a new and an older CL], treatments did not differ in causing complete luteolysis. Furthermore, complete luteolysis in experiment 2 did not differ regardless of whether cows had 1, 2, or 3 or more CL before PGF2α administration. Pregnancy per AI did not differ among treatments, indicating that any of the 3 treatments might produce similar pregnancy outcomes with the flexibility of applying either of the 7- or the 8-d treatments.